Dissolution and enchantment on Erwin Straus' phenomenology of obsession - Federico Leoni (Revista Latinoamericana de Psicopatologia Fundamental)
The author presents Erwin Straus’ psychopathology of phoby and obsession (with reference to his texts On Obsession, Phenomenology of Hallucinations, and Vom Sinn der Sinne), bringing to light the implications concerning the role of language and gesture in the consistution (and the crisis) of the experiences of subjectivity and objectivity.